Histomorphometrical and histochemical study of small intestine development in local chicken (Gallus gallus domesticus) and duck (Anas platyrhynchos domesticus) embryos (NTU Journal of Agriculture and Veterinary Science, 2024)
This study demonstrated for the first time the histomorphometry of the small intestine (SI) and distribution of goblet and Paneth cells, collagen, and smooth muscle fibers in (SI) of the local chicken and duck during embryological development using the combined PAS and Alcian blue (pH2.5), Geimsa, and Masson's trichrome stains. One hundred and four fertilized chicken eggs and one hundred and forty fertilized duck eggs were collected from Mosul city. The sample placed in an incubator with automatic movement, ventilation, and humidity was (60%) and the temperature was (37.7 °C) for chicken and (37.5 °C) for duck. The histomorphometry showed significant differences between chicken and duck embryos at the 19th and 21st days of incubation of the villi's length, width, and apparent surface area. As for the epithelium height and the intestinal crypts, there were significant differences between chicken and duck embryos at the 18th and 20th days of incubation in the ileum and jejunum. Furthermore, the mucosa was thicker in chicken embryos in the day of hatching, the submucosa was thicker in ducks during the 18th day of the incubation in the duodenum. During day 15 of the incubation in chicken embryos in the jejunum and ileum, the muscularis layer was thicker in the duodenum and jejunum and less thick in the ileum, and the collagen fibers were less too in the duck embryos at hatching d. The serosa was thicker in the duck embryos. The percentage of the goblet cells was higher with a larger density in duck embryos  than chicken at hatching day. Paneth cells were characterized by acidic granular cytoplasm. The achieved outcomes of histomorphometry and the density variances of the glycoprotein secretion are probably linked with numerous definite roles of (SI) parts in the progressions of nutrient absorption.